Caracterização química, avaliação do potencial antioxidante, hipoglicemiante e antimicrobiano de Annona tomentosa R. E. Fr. (ANNONACEAE) - PINHEIRO, Aglaete de Araújo (2022)
Annona tomentosa R. E. Fr. is a non-endemic Annonaceae from Brazil, popularly known as “araticum” and traditionally used in the treatment of microbial and parasitic infections, pain and inflammation. However, there are few studies reported about its chemical composition and pharmacological evaluation. The objective of this work was to carry out the phytochemical study and evaluate the biological potential, from antioxidant, enzymatic, antimicrobial, cytotoxic (in vitro) and acute toxicity (in vivo) tests of the crude extract and acetate and alkaloid fractions of the stem bark of A. tomentosa. The analysis of the methanolic extract (EM-AT) by Liquid Chromatography coupled to Mass Spectrometry (LC-MS), led to the identification of eleven compounds belonging to the classes of phenolic acids, flavonoids and alkaloids, most of them identified for the first time in species. In the evaluation of the antioxidant potential, by the DPPH and ABTS methods, EM-AT and the ethyl acetate fraction (FAC-AT) inhibited the radicals (>50%) at the highest concentration evaluated (10.0 µg/mL), of dose-dependent form and with low mean inhibitory concentration (IC50), at the same concentrations as the standard. Regarding the enzymatic inhibition capacity of α-glucosidase, only EM-AT showed activity, exhibiting inhibition above 95%, greater than that of Arcabose, at concentrations of 52.63 and 26.31 μg/mL. As for antimicrobial activity, all samples evaluated showed promising results. By the agar diffusion test, FAC-AT exhibited an inhibition halo (18.0 ± 1.41 mm) greater than the control Imipenem (IMP) (16.5 ± 9.0 mm) for Escherichia coli, and, by microdilution, FAC-AT showed minimum inhibitory concentrations (MIC) of 10.4 µg/mL, lower than those of the drugs IMP (12.5 ± 0.00 µg/mL) and Fluconazole (FLZ) (13.3 ± 0.00 µg/mL). 4.62 µg/mL) for Staphylococcus aureus and Candida albicans. In addition, the alkaloid fraction (FA-AT) also presented MIC (12.5 ± 0.00 µg/mL) lower than the FLZ control (13.3 ± 4.62 µg/mL) for C. albicans. In the microbial biofilm assay, EM-AT exhibited the best results. For S. aureus, it showed a significant reduction in 4×MIC90 (p<0.0001), and for C. albicans, it showed more significant results (p<0.0001) than the positive control FLZ. In the cytotoxic assay in sheep erythrocytes and acute toxicity in Tenebrio molitor larvae, the results showed correlation, in a concentration range between 1.0 and 100.0 µg/mL and µg/Kg, respectively. The extract and fractions did not show relevant toxicity against the alternative model of invertebrates. The therapeutic potential allied to the low toxicity of the extract and fractions open promising perspectives for the exploration of the species A. tomentosa, aiming at the development of products from extracts, fractions and/or isolated molecules, which are effective and less toxic.